1984
DOI: 10.1097/00000658-198407000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy for Hematologic Disease

Abstract: Between 1956 and 1981, 306 splenectomies for hematologic diseases were performed at the UCLA Medical Center. Of these operations, more than 75% were performed for therapeutic reasons to control anemia, thrombocytopenia, neutropenia, or painful symptoms of splenomegaly. Of the 65 patients who had idiopathic thrombocytopenic purpura, 77% showed an excellent response, and of the 39 patients who had hereditary spherocytosis, 90% responded. Other diseases with predictably good response rates were autoimmune hemolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(26 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The 20% mortality rate associated with splenec tomy found in the present series is in agreement with the figures reported by others, that range from 10 to 20% [2, 5-13, 16, 17, 19], The high mortality and mor bidity after splenectomy in IM compared with other hematological disorders is well known [17], Finally, as in previous studies, infectious, thrombotic and hem orrhagic complications were the most frequent causes of death in our patients.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The 20% mortality rate associated with splenec tomy found in the present series is in agreement with the figures reported by others, that range from 10 to 20% [2, 5-13, 16, 17, 19], The high mortality and mor bidity after splenectomy in IM compared with other hematological disorders is well known [17], Finally, as in previous studies, infectious, thrombotic and hem orrhagic complications were the most frequent causes of death in our patients.…”
supporting
confidence: 93%
“…In patients with either cytopenia secondary to hypersplenism or painful splenomegaly, splenectomy can be a useful measure [2,6,9,13,16,17]. Some authors also include portal hypertension secondary to splenomegaly among the indications for splenectomy in IM [5,7,12], It must be pointed out, however, that the influ ence of splenectomy on both the disease evolution and the patients' survival is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Literature shows post splenectomy complications rate ranging from 12% to 52% while mortality rates ranging from 1% to 9%. For example, Musser et al 12 reported a complication rate of 25% and mortality rate of 5%, Dawson et al 13 reported a morbidity of 25%, and mortality of 1%, Similarly, Johansson et al 14 described various complications in 14.5% patients with mortality of 1%. Recent studies show more favorable results, like Kojouri et al, in an analysis of 3386 splenectomies, reported a complication rate of 9·6% for laparoscopic splenectomy and 12·9% for open splenectomy, while associated mortality rates were very low, at 0·2% and 1% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Splenectomy has been performed for a heterogeneous group of hematologic diseases with a therapeutic or diagnostic purpose or as part of the staging process in Hodgkin's disease. Splenectomy has proved to be safe and effective in selected patients presenting non-Hodgkin's lymphoma, idiopathic thrombocytopenic purpura, thrombotic thrombocytopenic purpura, and hairy cell leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective studies of splenectomy for hematologic disease show complication rates that range between 13% and 52%, with mortality rates ranging from 1% to 9%. 1,4,8,9 Musser et al 1 reported a complication rate of 25% and a 5% mortality rate in 306 splenectomies performed at the University of California, Los Angeles, with 19% of the procedures performed for diagnostic reasons only. The authors also acknowledge that significantly fewer complications were observed in patients undergoing diagnostic splenectomy.…”
Section: Introductionmentioning
confidence: 99%